Simulation of the thermal and electrical performance of a novel PVT-PCM system - Chen, Tianyu (2018)
This study provides an insight into the fundamentals of PV performance enhancement under different environmental conditions. The study also presents a new concept of PCM integrated PVT system which has a better performance from both electrical and thermal perspectives.